Biallelic Parkin (PARK2) mutations can cause a bvFTD phenotype without clinically relevant parkinsonism. (October 2018) - Zimmermann, Milan; Wilke, Carlo; Schulte, Claudia; Hoffmann, Jessica; Klopfer, Jasmin; Reimold, Matthias; Brockmann, Kathrin; Synofzik, Matthis
Highlights: The phenotypic spectrum of Parkin mutations is larger than previously assumed. It can include predominant bvFTD phenotypes with only mild parkinsonism, with disease onset above 50 years. Frontotemporal networks are vulnerable to Parkin disease.